Prevalencia y detección de los trastornos depresivos en atención primaria - Gabarrón Hortal, E. (Aten Primaria, 2002)
AIM: To study the prevalence of depression in primary care, the detection of depressive disorders by primary care physicians, and the factors that influence detection. DESIGN: Cross-sectional, descriptive study. SETTING: Gavà II Primary Care Center, in Barcelona, Spain. PARTICIPANTS: A total of 400 people between the ages of 18 and 65 years were chosen randomly from among those who attended appointments with their primary care physician. MAIN MEASURES: A sociodemographic questionnaire and the Beck Depression Inventory (BDI) screening test were administered, and the participant´s medical record was reviewed. In a subsample of 40 participants, the Mini-International Neuropsychiatric Interview (MINI) was also administered. The optimum cutoff score for the BDI was estimated with reference to the MINI results. RESULTS: A cutoff score of 20/21 for the BDI had a sensitivity of 86.7% and a specificity of 92%, when the MINI score was used as a reference. The adjusted prevalence of depressive disorder in our primary care setting was 20.2% overall, 8.1% in men, and 26.8% in women (odds ratio 4.15, p < 0.01). The physician detected depressive symptoms in 55.7% of all likely cases of depression. Persons who scored (3) 21 on the BDI made more visits to their primary care physician, and had more stressful life events, than those who scored £ 20. CONCLUSIONS: The prevalence of depression in our primary care setting is high. The disorder was underdiagnosed in as many as 44.3% of the persons likely to have depressive disorder (especially women, widows and widowers, retired persons, persons who had experienced stressful life events, and frequent users of primary care services).